2019
DOI: 10.1016/j.anai.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

ω-3 LCPUFA supplementation during pregnancy and risk of allergic outcomes or sensitization in offspring

Abstract: Background: Allergic diseases have seen a rise worldwide in the last two decades, with children suffering the highest burden of the condition. The ω-3 Long-Chain Poly-Unsaturated fatty Acid (LCPUFA) poses anti-inflammatory properties that could lead to a reduction in inflammatory mediators in allergies. Objective: A systematic review and meta-analysis of the most recent follow-ups of randomised controlled trials (RCTs) was conducted to assess the effectiveness of ω-3 LCPUFA supplementation started during pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 57 publications
5
38
0
Order By: Relevance
“…We did not find a significant effect on any allergic sensitization outcome. The discrepancy may be attributed to the fact that one of the studies included by Vadhaninia et al 126 was excluded from our review, as maternal supplementation continued up to 2.5 months post-delivery. 127 Our findings are also different from the conclusions drawn by Garcia-Larsen et al 13 The difference probably lies in the choice of studies included in each systematic review.…”
Section: Comparison Of Findings To Previous Studiesmentioning
confidence: 96%
“…We did not find a significant effect on any allergic sensitization outcome. The discrepancy may be attributed to the fact that one of the studies included by Vadhaninia et al 126 was excluded from our review, as maternal supplementation continued up to 2.5 months post-delivery. 127 Our findings are also different from the conclusions drawn by Garcia-Larsen et al 13 The difference probably lies in the choice of studies included in each systematic review.…”
Section: Comparison Of Findings To Previous Studiesmentioning
confidence: 96%
“…Differences might be due to assessment of PUFAs in groups versus patterns, or the age at which asthma was assessed, at a younger age, as it is difficult to distinguish asthma from a viral-induced wheeze. A recent literature-based meta-analysis of randomized controlled trials mainly included studies with a follow-up until infancy and did not find a beneficial effect of n-3 PUFA supplementation in pregnancy on wheezing or asthma in the children [ 23 ]. Randomized controlled trials with a longer follow-up until school-age or young adulthood suggested that prenatal n-3 PUFA supplementation reduced the risk of asthma, although no consistent effect on lung function or allergy development was observed [ 6 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent pertinent meta-analysis of seven intervention trials with 2047 children, it was confirmed in a slightly less pronounced manner that EPA and DHA in pregnancy reduce asthma and persistent wheezing in the child [46]. Epidemiologic studies and some, but not all, intervention trials demonstrated that EPA and DHA in pregnancy can reduce the propensity towards allergies in the children [52][53][54][55].…”
Section: Clinical Benefit Of Omega-3s In Pregnancymentioning
confidence: 99%